The formation of UDC database for the automated system for managing union theme and typological plan of acquisition in the Centralized Library System of the Library on Natural Sciences of the Russian Academy of Sciences - E. N. Bocharova; A. A. Ivanovskij (Библиосфера)
Considered is the system for forming the database for the automated systems of managing the union theme and typological plan of acquisition in the Centralized Library System of the Library on Natural Sciences of the Russian Academy of Sciences. Such records fulfill reference and information functions. They allow any specialist freely rely in the structure of modern scientific knowledge.